O‘ZBEK DRAMATURGIYASI ASOSCHISI THE FOUNDER OF UZBEK DRAMATURGY (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article provides information about Hamza Hakimzoda Niyazi's great contribution to Uzbek dramaturgy.